Optimalisasi Tumbuh Kembang Bayi dengan Stimulasi melalui Pijat Bayi - Cahyaningrum; Hardyani (INDONESIAN JOURNAL OF COMMUNITY EMPOWERMENT (IJCE), 2024)
Infancy is a golden period of growth and development, so optimal quality of growth and development is very important. Baby massage has various benefits such as increasing the frequency of breastfeeding, increasing the baby's weight, making the baby more relaxed, making sleep deeper and longer and can even increase immunity. baby's body. Furthermore, when parents massage their babies independently, at the same time the parents also provide auditory stimulation (hearing, by inviting the baby to talk while being massaged), visual stimulation (sight, by making eye contact while massaging) and so on. so that the bond between parent and baby becomes stronger. Based on this situation, we carried out community service activities about the importance of knowing baby massage and its various benefits, targeting parents who have babies aged 0-12 months. It is hoped that this activity can become a forum. in increasing parents' knowledge and skills in carrying out baby massage independently at home. After the service was carried out, all respondents or 10 (100%) answered correctly about the meaning of baby massage, the benefits of baby massage and when is the right time to do a baby massage, 10 respondents (100%) answered correctly about when massage can be done, 9 respondents (85.7%) answered correctly about contraindications for infant massage. Respondents understood baby massage techniques and began to do and practice them independently at home with video guidance on baby massage techniques provided by the community service team.   ABSTRAK                 Masa bayi adalah masa keemasan dalam pertumbuhan dan perkembangan, sehingga kualitas tumbuh kembang yang optimal sangatlah penting.. Pijat bayi memiliki berbagai manfaat seperti meningkatkan frekuensi menyusu, meningkatkan berat badan bayi, membuat bayi lebih relaks, membuat tidur lebih lelap dan lama bahkan dapat meningkatkan kekebalan tubuh bayi. Lebih jauh lagi, ketika orang tua memijat bayinya secara mandiri, pada saat yang sama orang tua juga melakukan stimulasi auditory (pendengaran, dengan mengajak bayi bicara saat dipijat), stimulasi visual (penglihatan, dengan mengadakan kontak mata saat memijat) dan lain-lain, sehingga ikatan (bonding) antara orang tua dan bayi semakin erat. Berdasarkan situasi tersebut, maka kami melakukan kegiatan pengabdian masyarakat tentang pentingnya mengenal pijat bayi beserta beragam manfaatnya dengan sasaran orang tua yang memiliki bayi usia 0-12 bulan. Diharapkan dengan kegiatan ini dapat menjadi wadah. dalam meningkatkan pengetahuan dan keterampilan orang tua dalam melakukan pijat bayi secara mandiri di rumah. Setelah di lakukan pengabdian, Seluruh responden atau  10 (100%) menjawab dengan benar tentang pengertian pijat bayi manfaat pijat bayidan  kapan waktu yang tepat untuk dilakukan pijat bayi sebanyak 10 responden (100%) menjawab dengan benar tentang kapan pemijatan dapat dilakukan, sebanyak 9 responden (85,7%) menjawab dengan benar tentang kontraindikasi dari pijat bayi. Respasponden memahami teknik pijat bayi dan mulai melakukan dan mempraktekkan secara mandiri di rumah dengan panduan video teknik pijat bayi yang diberikan tim pengabdian